1987
DOI: 10.1161/01.hyp.9.4.371
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the cardiovascular effects of arginine vasopressin in conscious dogs.

Abstract: SUMMARYThe effects of physiological elevations in arginine vasopressin on the cardiovascular system were studied in a group of nine conscious, chronically instrumented dogs. The animals were studied under normal conditions (plasma vasopressin, 4.1 ± 0.4 pg/ml), after 24 hours of dehydration (plasma vasopressin, 7.3 ±1.5 pg/ml), after a 30-minute vasopressin infusion at 2.6 ng/kg/min (plasma vasopressin, 62.8 ± 10.3 pg/ml), and after a 4-day vasopressin infusion at 2.6 ng/kg/min (plasma vasopressin, 96.6 ±8.1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…These results are in agreement with a study carried out in conscious dogs using doses of AVP similar to those used in our study (Tipayamontri, Young, Nuwayhid and Scott 1987). The discordant results between our study and previous studies in humans (Aylward et al 1986) may be related to the higher doses of AVP used by these authors.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with a study carried out in conscious dogs using doses of AVP similar to those used in our study (Tipayamontri, Young, Nuwayhid and Scott 1987). The discordant results between our study and previous studies in humans (Aylward et al 1986) may be related to the higher doses of AVP used by these authors.…”
Section: Discussionsupporting
confidence: 92%
“…Thirdly, it is likely that either increased TPR may rise cardiac afterload leading to a fall in cardiac output and/or increased RVR may decrease venous return with ensuring the reduction in cardiac output. Indeed, Tipayamontri et al (1987) reported that AVP increased both RVR and TPR, leading to a fall in cardiac output in dogs. Therefore, taken together, it appears likely that all the mechanisms above-mentioned may be possible explanations for the hypoeffective heart observed in the present study as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AVP seems to retain a long-term vasoconstrictor effect, since the injection of VI antagonist decreased total peripheral resistance and increased cardiac output and heart rate. In additional studies, 4-day infusions of AVP failed to alter arterial pressure or total peripheral resistance in spite of the marked elevation of plasma AVP concentration to 97 pg/ mL (Tipayamontri et al 1987). Thus, the haemodynamic consequences of chronic AVP infusion may vary with the experimental conditions.…”
Section: Discussionmentioning
confidence: 92%
“…To determine whether chronic excess of AVP produces persistent elevation of arterial pressure, the long-term effects of exogenous infusion of AVP have been investigated (Brown et al 1986;Cowley et al 1986;Hall et al 1986;Liard 1987;Tipayamontri et al 1987). Although most of these experiments revealed the persistent vasoconstrictor and/or antidiuretic effects of AVP, the ability of AVP to produce sustained elevation of arterial pressure was not demonstrated consistently.…”
Section: Introductionmentioning
confidence: 99%